Fitrat (Human Nature) and Child - DEMİRCİ, Mehmet (Scientific Journal of Faculty of Theology, 2022)
The concept of “fitrat” (human nature) both describes creation and reveals a value for the created. In this respect, it is one of the basic concepts of Islamic thought. Therefore, it is important to examine the concept on its own and to reveal its various dimensions. In this study, “fitrat” (human nature) was first discussed and analyzed in terms of its conceptual aspect, then research, examination and evaluations were made about the place and importance of “fitrat” in the thought of the Qur'an. In this context, the position of man in the universe and the basis of his human nature, the characteristics of human nature, the importance of preserving and developing human nature were discussed. Since the concept of “fitrat” in Islamic thought is closely related to childhood, studies and research on the relationship between them are included in the study. In this part, especially the religious dimension of childhood nature was included. In this context, the feeling of belief in childhood and the factors that reveal this feeling and how these affect the religious development of children were discussed. Then, the relationship between the religiosity of adults and “fitrat” (human nature) was examined.